(untitled) (Medico Legal Update, 2020)
The aim of this research was to identify the role of mycoplasma bacteria in eyes infections. A 100 samples were isolated from patients whom suffering from eye infections for 2nd Jan - 30th June 2018 . The clinical isolates were cultivated on mycoplasma media . Biochemical tests were then performed. Three types of mycoplasma were isolated (M.pneumoniaein 42 cases, M.salivariumin 30 cases & M.hominisin three cases). Six cases were recorded single infection . The highest incidence of mycoplasma in the age group (11-20 years).